The plague of fantasies - Zizek, Slavoj, 1949- (London ; New York : Verso, 1997)
Slavoj Zizek claims that the current age in which we live is plagued by fantasms in the form of digitized imagery and the increasingly abstract nature of daily life. He explores the relationship between fantasy and ideology.
Reissued with a new preface by the author - Main text originally published: 1997.
Includes index.
boek